Analysis of the Influence of GRDP, Population, Unemployment Rate, and the Covid-19 Pandemic on Poverty - Fathurahman, Mochamad Arbi; Marlina Ekawaty (Journal of Development Economic and Social Studies, 2025)
This study aims to analyze the effect of Economic Growth, Population, Open Unemployment Rate, and the Covid-19 Pandemic on Poverty in East Java Regency/Province in 2019-2023. This study uses a quantitative approach with a panel data regression analysis method. The data obtained in this study are secondary data processed and sourced from the Central Statistics Agency (BPS) website. The type of data in this study is panel data. This study implies that policymakers in East Java must focus on efforts to maintain and increase economic growth and manage population dynamics effectively in order to reduce poverty levels. In addition, efforts to reduce open unemployment through job creation and workforce development are essential. Furthermore, strategies to mitigate the adverse socio-economic impacts of the Covid-19 pandemic, such as social protection programs and economic recovery initiatives, are critical to prevent further increases in poverty. These recommendations aim to support comprehensive poverty reduction in the region during and after the pandemic.